MOF-derived formation of nickel cobalt sulfides with multi-shell hollow structure towards electrocatalytic hydrogen evolution reaction in alkaline media. (15th November 2019) - Wu, Caiyun; Du, Yunmei; Fu, Yunlei; Wang, Wensi; Zhan, Tianrong; Liu, Yanru; Yang, Yu; Wang, Lei
Abstract: In this work, nickel cobalt bimetallic sulfide with typical multi-shell hollow sphere structure behaved superior electrocatalytic activity towards hydrogen evolution reaction (HER), which have been prepared through a easy method included solvothermal step, calcination step and in-situ sulfurization step. The composition and structure of the obtained nickel cobalt bimetallic sulfide are controlled through adjusting the sulfurization temperature and dosage of sulfur source. The as-prepared Ni–Co-S multi-shell hollow microspheres (abbreviated as Ni-Co-S) behaves superb HER properties in alkaline medium and Ni-Co-S-340(60) performs the most superior property, in which reflected the lowest overpotential (129 mV vs. RHE) at the current density of 10 mA cm −2 and the smallest Tafel slope (96.1 mV dec −1 ) among all the synthesized samples. The superior electrocatalytic performance of the obtained Ni-Co-S-340(60) for HER is owing to the unique multi-shell hollow structure derived from the intrinsic porous character of Ni-Co-BTC MOF precursor in one hand. And in the other hand, introducing highly active NiCo2 S4 into NiS2 would enhance its elctrocatalytic activity because of the strong interfacial effect between NiS2 and NiCo2 S4 . Graphical abstract: Image 1